Emulsions preparation based on ternary phase diagrams: comparative study using two oils (Miglyol and sweet almond) with two distinct surfactants (Tween 80 and Saponin) - Schreiner, Tatiana B. (2018)
An emulsion is a colloidal dispersion composed by a mixture of two immiscible liquids, being one the dispersed phase, as droplets, and the other one the continuous phase. In this work, a comparative study comprising the surfactants Tween 80 (synthetic surfactant) and Saponin (natural surfactant) and the oils Miglyol 812 and Sweet Almond was performed. The development of emulsions based on ternary phase diagrams showed that different phases can be formed giving rise to different formulations: microemulsions, gels, and mixtures with 1, 2 and 3 phases. The application of the HPH technique produced stable nanoemulsions with narrow distributions. Considering Tween 80, and comparing the two oils, Miglyol 812 gave rise to emulsions with lower particle size (0.023μm), comparatively to Sweet Almond Oil (1.009μm). This difference can be related with the oil viscosity, which is lower for Miglyol 812. Comparing the two surfactants, natural Saponin was very effective in the o/w composition range.